2021
DOI: 10.3390/metabo11080514
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Long-Lasting Effects of Fetal Nutrient Restriction versus Exposure to an Obesogenic Diet on Islet-Cell Mass and Function

Abstract: Early life represents a window of phenotypic plasticity. Thus, exposure of the developing fetus to a compromised nutritional environment can have long term consequences for their health. Indeed, undernutrition or maternal intake of an obesogenic diet during pregnancy leads to a heightened risk of type 2 diabetes (T2D) and obesity in her offspring in adult life. Given that abnormalities in beta-cell function are crucial in delineating the risk of T2D, studies have investigated the impact of these exposures on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 107 publications
0
6
0
Order By: Relevance
“…As a consequence, many organoids still represent a developmental stage rather than a mature organ 10 . As there is genetic evidence that perturbed development of the pancreas can predispose to diabetes mellitus 11 and numerous studies have shown that the environment of the fetus during pregnancy programmes adult metabolic activity 12 , organoids mimicking pancreas development are useful to study these mechanisms. Here we focus on the pancreas, a central organ in diabetes mellitus, and briefly introduce its development.…”
Section: Modelling Pancreas Developmentmentioning
confidence: 99%
“…As a consequence, many organoids still represent a developmental stage rather than a mature organ 10 . As there is genetic evidence that perturbed development of the pancreas can predispose to diabetes mellitus 11 and numerous studies have shown that the environment of the fetus during pregnancy programmes adult metabolic activity 12 , organoids mimicking pancreas development are useful to study these mechanisms. Here we focus on the pancreas, a central organ in diabetes mellitus, and briefly introduce its development.…”
Section: Modelling Pancreas Developmentmentioning
confidence: 99%
“…Data also implicate impaired mitochondrial metabolism, oxidative stress, mammalian target of rapamycin signaling, epigenetic deoxyribonucleic acid modifications, and microRNAs in the impaired b-cell adaptability after gestational nutrition restriction. 79 Taken together, the combination of prenatal undernutrition with postnatal overnutrition and catch-up growth is detrimental for rodent metabolic risk, as it is for human.…”
Section: Postnatal Overnutrition Increases Pancreatic B-cell Massmentioning
confidence: 99%
“…The impact of restricted fetal growth on β‐cell growth and development has been studied in animal models, such as maternal protein deficiency and uterine artery ligation 79 . Offspring with gestational undernutrition are more consistently observed to have increased risk for IGT and type 2 diabetes than offspring exposed to gestational overnutrition 79 .…”
Section: In Rodents Postnatal Overnutrition Expands β‐Cell Mass But H...mentioning
confidence: 99%
See 1 more Smart Citation
“…In a detailed review, O'Hara et al discussed our current understanding of fetal exposure to either maternal caloric excess or nutrient restriction. Significantly, they discussed the effects of fetal malnutrition with respect to multiple outcomes, from mitochondrial metabolism to islet morphology and beta-cell function and the consequences for Type 2 Diabetes development [10].…”
mentioning
confidence: 99%